(untitled) (KYAMC Journal, 2017)
Epidural anaesthesia is a very popular method of anaesthesia and post-operative analgesia for cardiac compromised pregnant patient all over the world. In our case Mrs. Akhi 34 years pregnant women admitted in KYAMCH on 13.03.2017 with 37 weeks pregnancy. She has a long history of Rheumatic fever followed by Rheumatic heart disease, severe MS (mitral stenosis) after that she was operated CMC (Close Mitral Commissurotomy) in 2012. She was admitted with respiratory distress at KYAMCH, with pregnancy on December 2016. After that she was under close supervision of cardiac surgery and Gynae and Obstetrics department. After admission on 13.03.2017 she was evaluated by the department of anaesthesia and graded as ASA (American Society of Anaesthesia) class-4. And selected for routine case of caesarean section on 14.03.2017. Operation was done under epidural anaesthesia and post-operative analgesia was maintained by epidural catheter. KYAMC Journal Vol. 8, No.-1, Jul 2017, Page 69-71